PARAMETRIC AND AUTO-STEWED PROCESSES IN THE SURFACE LAYERS OF PARTS AS EXTERNAL SOURCES OF THEIR DESTRUCTION DURING FRICTION AND WEAR - Malinovskyi, Yurii; Mikosianchyk, Oksana; Vlasenkov, Dmyro; Sytnyk, Serhii; Rybak, Dmitro; Oliinyk, Svitlana; Berezivskyi, Nazarii (Problems of Friction and Wear, 2025)
During the execution of various technological processes and the operation of general-purpose actuators, oscillatory movements may occur that are excited without a source of oscillatory motion. These oscillations usually occur either in the area where the two parts come into contact or in the area ahead of the leading edge of the moving part. The oscillatory nature of the movements in the contact area of the parts and the area ahead of the leading edge of the moving part have different physical nature. Thus, in the area of interaction of parts (on the contact pad), oscillatory movements occur due to the unsteady characteristic of friction, which depends on the sliding speed of the parts. At certain ratios of sliding speeds, self-oscillatory motions can appear or disappear, as well as be strengthened or weakened. These oscillations are one of the causes of unregulated roughness, (deformation) cracking and peeling of interacting parts, as well as significant dynamic components during loading of actuators, drives and power mechanisms. Self-oscillations in the surface layers of parts with deformation wave formation, which leads to further destruction in these layers, ahead of the front edge of the die due to the formation of residual plastic waves and subsequent destruction of their crests. Due to the dynamic nature of the interaction between the parts during friction, the force acting on the contact line between the die and the extended part exceeds the critical Euler force and is actually a parametric load, accompanied by the phenomenon of parametric resonance, which usually has a more dangerous effect than the usual resonance during forced vibrations. Therefore, the destruction of the surface layer of parts under parametric resonance is more significant. The main vibration frequency at which parametric resonance occurs is equal to twice the frequency of bending vibrations of the beam-strip. The frequency region near the parametric resonance frequency is the main area of dynamic instability ahead of the moving die. In this problem, we consider frictional self-oscillations in the area under the die, which are a source of loss of dynamic stability in the area in front of the die, development of parametric vibrations of the surface layers of parts and a number of cases of parametric vibrations and parametric resonance of the outer layers of parts that are destroyed during interaction. The connection between frictional and parametric vibrations is established through two adjacent sections of the beam-strip in its stretched and compressed parts.